In vitro study of coronary flow occlusion in transcatheter aortic valve implantation - He, Zheng-Fu; Zhang, Wei-Ming; Lutter, George; Quaden, Rene; Cremer, Jochen; Cai, Xiu-Jun (Journal of Thoracic Disease, 2014)
Background: Transcatheter aortic valve implantation (TAVI) has been developed recently for patients with high morbidities and who are believed to be not tolerate standard surgical aortic valve replacement. Nevertheless, the TAVI is associated with complications such as potential obstruction of coronary ostia, mitral valve insufficiency, and stent migration although it seems promising. Impairment of the coronary blood flow after TAVI is catastrophic and it was believed to be associated with the close position of the coronary orifice and the aortic leaflets and valve stent. However, few data was available as to the anatomic relationship between valve stent and aortic root anatomic structures including the coronary arterial ostia, aortic leaflets. Methods: The aortic roots were observed in 40 hearts specimens. The width of aortic leaflet, height of aortic sinus annulus to the sinutubular junction (STJ), distance between aortic sinus annulus to its corresponding coronary ostia, and coronary arterial ostia to its corresponding STJ level were measured. Moreover, the relationships of valve stent, aortic leaflets and coronary ostia before/post stent implantation and after the open of aorta were evaluated respectively. Results: Approximate three quarters of the coronary ostia were located below the STJ level. The mean distances from left, right and posterior aortic sinus annulus to the related STJ level was comparable, which was 18.5±2.7, 18.9±2.6, 18.7±2.6 mm, respectively. Meanwhile, the height of left and right aortic sinus annulus to its corresponding coronary ostia was 16.6±2.8 and 17.2±3.1 mm for left and right side respectively. Conclusions: Most of the coronary ostia were located below the STJ level and could be covered by the leaflets. This highlights the need of modified stents to prevent occlusion of coronary flow after TAVI.